Kekerasan dalam Rumah Tangga Kristen dan Dampaknya terhadap Keharmonisan Keluarga di Gereja Kingmi Jemaat Sejahtera Klasis Nabire - Tebun, Mince (CV. Creative Tugu Pena, 2024)
This article discusses Christian families who commit Domestic Violence (KDRT) and its impact on family harmony. The purpose of this writing is to determine the impact of domestic violence on family harmony at the Kingmi Church, especially the Nabire Sejahtera Congregation, as well as the steps that the Church has taken to overcome domestic violence. This research was carried out at the Nabire Prosperous Congregation Kingmi Church. Using a qualitative method approach, research shows that there are many Christian families who commit domestic violence, the forms of violence carried out are physical violence and psychological violence. The factors that cause violence include: gambling, alcohol, economics, lack of premarital counseling, jealousy, differences of opinion, social culture, and arranged marriages. From the research results, the author concludes that domestic violence can cause disharmony in the family, where there is no peace, harmony, indifference between family members, and lack of good communication within the family. Keywords: Christian Family, Domestic Violence, Family Harmony